Screening and risk reducing surgery for endometrial or ovarian cancers in Lynch syndrome: a systematic review. Issue 5 (18th April 2022) - Lim, Natalie; Hickey, Martha; Young, Graeme P; Macrae, Finlay A; Kelly, Christabel
Abstract : Objective: Lynch syndrome is a hereditary cancer syndrome caused by mismatch repair gene mutations, and female carriers are at an increased risk of endometrial and ovarian cancer. The best approach to screening is not yet clear and practice varies across countries and centers. We aimed to provide evidence to inform the best approach to screening and risk reduction. Methods: A systematic search of the literature was conducted (Medline, Embase, PubMed). Studies evaluating the following were included: women with Lynch syndrome (by mismatch repair mutation or Amsterdam II criteria), screening methods for endometrial and/or ovarian cancer, intervention included endometrial biopsy, transvaginal ultrasound, or serum cancer antigen 125 (CA-125), outcomes evaluated were number of cancers and/or endometrial hyperplasia. Results: A total of 18 studies of Lynch syndrome carriers which screened for endometrial cancer using transvaginal ultrasound and/or hysteroscopy/endometrial biopsy revealed an incidence of 3.9% at the time of screening. Most (64.1%) endometrial cancers detected were from screening, with the balance detected in symptomatic women at the first screening visits, regular review, or between screening intervals. In mismatch repair carriers, the overall sensitivity of endometrial screening was 66.7%, and the number needed to screen ranged between 4 and 38 (median 7). The sensitivity of endometrial biopsy was 57.1% and the number needed to screen was 23–380 (median 78). The sensitivity of transvaginal ultrasound was 34.4% and the number needed to screen was 35–973 (median 170). Fourteen studies which screened for ovarian cancer using transvaginal ultrasound and/or CA-125 revealed an incidence of 1.3% at the time of screening and 42.9% of ovarian cancers were detected at asymptomatic screening. The sensitivity of ovarian screening was 54.6%, and the number needed to screen was 9–191 (median 23) in mismatch repair carriers. Thirteen studies reported 5.8% incident endometrial cancers and 0.5% ovarian cancers at time of risk reducing surgery. Conclusions: There is limited evidence to support screening for endometrial and ovarian cancer in Lynch syndrome and data on mortality reduction are not available. Further prospective, randomized trials comparing targeted screening methods are needed. Risk reducing surgery remains the most reliable way to reduce endometrial and ovarian cancer risk in Lynch syndrome.